Evaluation of trace metals and rare earth elements in mantis shrimp Oratosquilla oratoria collected from Shandong Province, China, and its potential risks to human health. (January 2021) - Jiao, Yanni; Yang, Luping; Kong, Zhengqiao; Shao, Lijun; Wang, Guoling; Ren, Xiaofei; Liu, Yongjun
Abstract: This study provided the primary data of selected trace elements and rare earth elements from 120 samples of mantis shrimp Oratosquilla oratoria ( O . oratoria ) caught from three sites in the Shandong Province, China and evaluated the potential health risk of shrimp consumption from this region. The calculation of estimated daily intake (EDI), target hazard quotient (THQ) and total target hazard quotient (TTHQ) showed that the contents of all target TREs were below respective permitted limits recommended by China, with the exceptions of Cd and iAs levels. In addition to pollution, results indicated that TREs concentrations in O . oratoria were also impacted by characteristics of O . oratoria . The distribution patterns of REEs in O . oratoria did not differ from those in the sediment and other marine organisms, following the abundance rule. Consumption of O . oratoria from Shandong Province is potentially harmful to human health due to high levels of Cd and iAs. Highlights: 15 trace and 14 rare earth elements were found in 120 mantis shrimp samples. Other than Cd and As, levels of all target TREs were below China's allowed limits. REE distribution in O. oratoria equal to those in sediment and other marine life. Consumption of O. Oratoria in Shandong may be harmful to human health. Cd and iAs concentrations in Mantis Shrimp in Shandong should be closely monitored.